Identification and characterization of tebuconazole transformation products in soil by combining suspect screening and molecular typology. (January 2016) - Storck, Veronika; Lucini, Luigi; Mamy, Laure; Ferrari, Federico; Papadopoulou, Evangelia S.; Nikolaki, Sofia; Karas, Panagiotis A.; Servien, Remi; Karpouzas, Dimitrios G.; Trevisan, Marco; Benoit, Pierre; Martin-Laurent, Fabrice
Abstract: Pesticides generate transformation products (TPs) when they are released into the environment. These TPs may be of ecotoxicological importance. Past studies have demonstrated how difficult it is to predict the occurrence of pesticide TPs and their environmental risk. The monitoring approaches mostly used in current regulatory frameworks target only known ecotoxicologically relevant TPs. Here, we present a novel combined approach which identifies and categorizes known and unknown pesticide TPs in soil by combining suspect screening time-of-flight mass spectrometry with in silico molecular typology. We used an empirical and theoretical pesticide TP library for compound identification by both non-target and target time-of-flight (tandem) mass spectrometry, followed by structural proposition through a molecular structure correlation program. In silico molecular typology was then used to group TPs according to common molecular descriptors and to indirectly elucidate their environmental parameters by analogy to known pesticide compounds with similar molecular descriptors. This approach was evaluated via the identification of TPs of the triazole fungicide tebuconazole occurring in soil during a field dissipation study. Overall, 22 empirical and 12 yet unknown TPs were detected, and categorized into three groups with defined environmental properties. This approach combining suspect screening time-of-flight mass spectrometry with molecular typology could be extended to other organic pollutants and used to rationalize the choice of TPs to be investigated towards a more comprehensive environmental risk assessment scheme. Graphical abstract: Highlights: Combined method to detect and categorize pesticide transformation products in soil. Detection by QTOF-MS of new tebuconazole transformation products without standards. Estimation by in silico molecular typology of their environmental parameters. Method to rationally choose relevant transformation products to be studied. The proposed approach could advance pesticide environmental risk assessment. Abstract : Combination of time-of-flight mass spectrometry and molecular typology is a novel and valuable approach to identify and categorize putative tebuconazole transformation products in soil.